2001
DOI: 10.1159/000045880
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Vaccination Profile of Hemodialysis Patients during an Outbreak of Hepatitis B Virus Infection

Abstract: During an outbreak of hepatitis B virus (HBV) infection in a hemodialysis unit, patients were assessed for serological viral markers and vaccination status. HBV infection was identified in 26 patients. Twenty of these were positive for hepatitis B surface antigen (HBsAg), and 6 were negative for HBsAg but positive for IgM antibody to hepatitis B core (anti-HBc) and HBV DNA. The primary source of infection was not clearly identified, although 2 patients were suspected to be the index cases. A multiple logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Another possibility is the absence, in the serology kits used, of an antigenic variant that is present in the geographic area studied (Dow et al 1996). Other studies also detected HCV or HBV nucleic acids in anti-HCV negative or HBsAg-negative/IgM anti-HBc-positive hemodialysis patients, respectively (Carneiro et al 2001, Lewis-Ximenez et al 2001. The potential problem of a high prevalence of HCV RNA positive patients in an HCV seronegative group deserves to be studied in depth, due to the possible consequences to HCV transmission in hemodialysis centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is the absence, in the serology kits used, of an antigenic variant that is present in the geographic area studied (Dow et al 1996). Other studies also detected HCV or HBV nucleic acids in anti-HCV negative or HBsAg-negative/IgM anti-HBc-positive hemodialysis patients, respectively (Carneiro et al 2001, Lewis-Ximenez et al 2001. The potential problem of a high prevalence of HCV RNA positive patients in an HCV seronegative group deserves to be studied in depth, due to the possible consequences to HCV transmission in hemodialysis centers.…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial transmission of HCV and HBV also appears to be an important contributing factor to the spread of these viruses (Castro-Figueiredo et al 1986, Teles et al 1998, Wreghitt 1999, Carneiro et al 2001. The prevalence of the HBV has drastically reduced with control practices, but outbreaks are still frequent and routine screening necessary (Wreghitt 1999, Lewis-Ximenez et al 2001.…”
mentioning
confidence: 99%
“…However, for others, HBV infection is still an important problem to patients (Vladutiu et al 2000, Otedo et al 2003, Kumar et al 2005. Nevertheless, HBV infection outbreaks are still seen when failures in infection control procedures occur (De Castro et al 2000, Lewis-Ximenez et al 2001.…”
mentioning
confidence: 99%
“…These data suggest that genotype D would be more likely to disseminate in the hemodialysis environment. In fact, although genotype A is the most prevalent genotype in Brazil, HBV genotype D strains have been involved frequently in hepatitis B outbreaks in dialysis units (Castro-Figueiredo et al, 1986;De Castro et al, 2000;Lewis-Ximenez et al, 2001;Roll et al, 1995), and in some of these cases they were probably more efficiently transmitted than genotype A (Castro-Figueiredo et al, 1986;De Castro et al, 2000;Teles et al, 2002). Additionally, several studies have shown a significant association of HBV genotype D and injection drug use (Fisker et al, 2004;Panessa et al, 2009;Swenson et al, 2001), reinforcing the idea that genotype D could be a blood-borne genotype.…”
Section: Hbv Variants In the General Population Vs Among Hemodialysimentioning
confidence: 99%